âFLATUSâ: FORMULA ANTI GALAU UNTUKMU SAHABAT - Choirunnisa, Amalia; Laily, Akhiril Fatiya Isnaenil; Baroroh, Avie Avievah; Anisa, Farahdiba; Hadwiono, Muhammad Reyhan (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Many young people in Indonesia are infected with virus